Catalytic reductive N-alkylation of amines using carboxylic acids. Issue 9 (16th December 2015) - Andrews, Keith G.; Summers, Declan M.; Donnelly, Liam J.; Denton, Ross M.
Abstract : We report a catalytic reductive alkylation reaction of primary or secondary amines with carboxylic acids. Abstract : We report a catalytic reductive alkylation reaction of primary or secondary amines with carboxylic acids. The two-phase process involves silane mediated direct amidation followed by catalytic reduction.